Peningkatan Kompetensi Guru dalam Penyusunan Soal HOTS melalui Workshop di MTs Negeri 5 Kulon Progo - Asnah Al Amien (Jurnal Pendidikan Madrasah, 2022)
This study aims to improve the competence of teachers in compiling Higher Order Thinking Skills (HOTS) questions through workshop activities. This research is an action research with the subject of the study being teachers at MTs Negeri 5 Kulon Progo. Data are collected through observation, interviews. This research was conducted in 2 cycles covering planning, implementation, observation, and reflection activities. The results showed an increase in teacher competence in compiling HOTS questions. In cycle I, the average value of studying HOTS questions was 86% increased to 94% in cycle II. This means that workshop activities can improve teacher competence in compiling Higher Order Thinking Skills questions.